Pengaruh Modal Intelektual, Struktur Modal dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan - Eny Purwaningsih; Euis Kurniawati (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study was conducted to analyze the influence of intellectual capital, capital structure, and sales growth on the financial performance of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2018-2020. The sample used in this study is food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2018-2020. This research data collection method uses secondary data. The sampling method used purposive sampling technique. Methods of data analysis using multiple regression analysis. Based the test results, it is simultaneously shows that financial performance, capital structure, and sales on financial performance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The partial test results show that intellectual capital has significant positive effect on financial performance, debt policy has significant negative effect on financial performance and sales growth has no significant effect on financial performance.